The Ontological Status of Psychopathology: an Overview (Culturas Científicas, 2022)
We analyze the ontological status of the notion of psychopathology derived from four methodological approaches to its study: psychiatric, phenomenological-existential, constructivist-historical, and anti-psychiatric. Using a systematized literature review methodology and following the metaframework ReSiste-CHS (Systematized Reviews in Human and Social Sciences), we will argue that this notion presents divergences in at least three points: (i) the relevance of symptomatology as a characteristic, (ii) the existence or non-existence of psychic suffering, and (iii) the relevance of social factors in its configuration. In the introductory section, we will address general historical considerations related to the study of mental disorders. In the second section, we will refer to the methodology used for the realization of the article. In the third section, we will present the fundamental features of the four study methodologies mentioned above, dividing the description into the following points: orientation, etiology, classification, diagnosis, and treatment. In the fourth section, we will contrast the concepts of psychopathology extracted from them. To conclude, we will propose a systematization of the minimum conditions that a notion of psychopathology must fulfill in order to be fruitful from a theoretical and practical point of view. These conditions include a critical stance against the reductionist and relativist extremes, the consideration of psychic suffering as a constitutive feature and fundamental core of this genre of experience, as well as an ethical dimension related to its approach. Finally, we will show some limitations and future directions derived from the work carried out.
Keywords: Psychopathology; Psychiatry; Phenomenology; Constructivism; Anti-psychiatry